Gait kinematics and kinetics in patients with different grades of meniscus injury: A cross-sectional study - Xinya Lan; Yaping Li; Jiaxin Gao; Yongyi Xu; Qingping Su; Pan Xu; Jianhao Chen; Zhonghua Lin; Cai Jiang (PLoS ONE, 2026)
Meniscal injuries are common and can alter knee biomechanics, increasing the risk of osteoarthritis. This study investigated the effects of unilateral meniscal injuries of different Stoller grades on gait kinematics and kinetics. A total of 158 participants were stratified by MRI into three groups: control group(Grade 0, n = 51), Grade I–II (n = 54), and Grade III (n = 53). Three-dimensional motion capture synchronized with force platforms was used to assess peak sagittal-plane joint angles, joint moments, and ground reaction forces. Multivariate analysis of covariance was applied to adjust for body mass index, Lysholm score, and walking speed. Compared with healthy controls, injured participants demonstrated reduced knee flexion, hip extension, and lower extremity joint moments, along with increased ankle dorsiflexion, knee extension, and hip flexion angles; anterior, posterior, and lateral ground reaction forces were also significantly decreased. Although no significant differences in joint moments or ground reaction forces were observed between Grade I–II and Grade III groups, deviations in joint angles increased gradually with the severity of injury. The most pronounced changes were seen in the knee extension angle, which rose by 309.0% in Grade III compared with the control group, and the hip extension angle, which decreased by 53.3% in Grade III compared with the control group. A 16.5% reduction in the knee flexion angle was also observed. These findings indicate that even mild meniscal injuries produce substantial gait kinetic deficits, while kinematic alterations become more pronounced with higher-grade injuries. The study highlights the value of integrating Stoller grading with objective gait analysis to identify functional impairments not captured by patient-reported outcomes. This comprehensive approach provides a biomechanical basis for early assessment and individualized rehabilitation strategies, supporting knee function preservation and potentially slowing long-term degenerative changes.